The influence of follicle numbers per ovary on the quality of oocytes and the day length of forming blastocyte s by in vitro fertilization - Sumantri, Cece; Anggraeni, Anneke (Indonesian Journal of Animal and Veterinary Sciences, 1999)
The aim of this research is to know the influence of the number of follicles produced per ovary on the quality of oocytes and the day length of developing blastocytes by in vitro fertilization (IVF) at 7-,8-, and 9-days. Material of the research is ovary of Fries Holland dairy cattle gathered from slaughterhouse. A number of 138 ovaries are grouped into four based on the number of follicles per ovary, including group I (â¤5 follicles), group II (6-10 follicles), group III (11-20 follicles), and group IV (â¥20 follicles). The result showed that the number of follicles per ovary are not significantly (P>0.05) influencing both on oocyte quality and the days length of forming blastocytes at 7-, 8-, and 9-days. Number of oocytes for grade A-B (percentage of the number of oocytes IVF per the number of oocytes obtained per ovary) for group I - IV consecutively is 83.5%, 91.3%, 97.1%, and 91.2%. The number of developing blastocytes (percentage the number of blastocytes per the number of oocytes) for group I - IV at 7-days consecutively is 5.19%, 5.56%, 5.45%, and 6.03%; at 8-days is 15.58%, 12.94 %, 13.64%, and 11.64%; at 9-days is 1818%, 8.96%, 8.18%, and 10.35%. Â  Key words: Oocytes, IVF, blastocyte